Brain substrates of early (4 h) cigarette abstinence: Identification of treatment targets. (1st January 2018) - Franklin, Teresa R.; Jagannathan, Kanchana; Hager, Nathan; Fang, Zhuo; Xu, Sihua; Wong, Joyce; Childress, Anna Rose; Detre, John A.; Rao, Hengyi; Wetherill, Reagan
Highlights: Regional Cerebral Blood Flow (rCBF) is reduced in corticolimbic regions during early abstinence vs recent smoking. Abstinence-induced changes may negatively impact neural processing. Across conditions, the change in rCBF correlated with the change in craving. Identifying early abstinence treatment targets has far-reaching implications. Abstract: Introduction: Research indicates that overnight nicotine abstinence disrupts neural activity in the mesocorticolimbic reward network; however, less is known about the time course of abstinence-induced brain changes. To examine the potential neural effects of early abstinence, we used arterial spin labeling perfusion fMRI, to measure regional cerebral blood flow (rCBF) changes in the resting brain induced by 4 h of nicotine abstinence. Methods: In a repeated measures design, 5 min of resting perfusion fMRI data were acquired in awake nicotine-dependent individuals (eyes open) during 'smoking as usual' (SMK) and following 4 h of monitored nicotine abstinence (ABS) conditions (N = 20). Conditions were compared using a paired t test in SPM8. Craving was assessed prior to each condition. Results: Compared to SMK, ABS significantly increased craving and reduced rCBF in select regions, including the hippocampus and ventral striatum (cluster corr, α = 0.01, 943 contiguous voxels). The magnitude of the abstinence-induced change in rCBF correlated with the magnitude of the change in craving across conditions in select regions, including the medial and lateral orbitofrontal cortices and the anterior ventral insula (r values ranging from 0.59–0.74). Conclusions: Results show that as few as 4 h of abstinence can reduce resting rCBF in multiple nodes of the brain's mesocorticolimbic network, disrupting neural processing. Identifying early withdrawal treatment targets has far-reaching implications, which include thwarting relapse proclivities. Results parallel those of the extant human literature and are in agreement with an extensive preclinical literature showing compromised mesolimbic dopaminergic function and impairments in reward function during nicotine withdrawal.